2002
DOI: 10.1177/107110070202301009
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Metatarsal Osteotomies: A Comparative Geometric Analysis Conducted on Sawbone Models

Abstract: We evaluated the change in position of the first metatarsal head using a three-dimensional digitizer on sawbone models. Crescentic, closing wedge, oblique shaft (Ludloff 8 degrees and 16 degrees), reverse oblique shaft (Mau 8 degrees and 16 degrees), rotational "Z" (Scarf), and proximal chevron osteotomies were performed and secured using 3-mm screws. The 16 degrees Ludloff provided the most lateral shift (9.5 mm) and angular correction (14.5 degrees) but also produced the most elevation (1.4 mm) and shortenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
0
17

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 3 publications
(3 reference statements)
2
67
0
17
Order By: Relevance
“…Complications, intraoperative and postoperative, have been reported at variable incidences, including troughing of the metatarsal, fracture, delayed union, rotational malunion, recurrence of deformity, and infection [4,12,14,20,21]. The nature of the osteotomy is more technically challenging, has a higher surgical learning curve, and requires meticulous attention to the threedimensional changes [17]. Smith et al [21] reported a 6% perioperative complication rate from their early experience to create awareness for those beginning to master the scarf osteotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Complications, intraoperative and postoperative, have been reported at variable incidences, including troughing of the metatarsal, fracture, delayed union, rotational malunion, recurrence of deformity, and infection [4,12,14,20,21]. The nature of the osteotomy is more technically challenging, has a higher surgical learning curve, and requires meticulous attention to the threedimensional changes [17]. Smith et al [21] reported a 6% perioperative complication rate from their early experience to create awareness for those beginning to master the scarf osteotomy.…”
Section: Discussionmentioning
confidence: 99%
“…However, it illustrates the need for further prospective comparative studies. Basically, proximal osteotomies are recommended for the treatment of moderate to severe deformities [3,[5][6][7]. The studies included in this meta-analysis also contained patients who suffered from mild to moderate hallux valgus deformity.…”
Section: Discussionmentioning
confidence: 99%
“…Mild deformity has less than 15°intermetatarsal 1-2 angle (IMA), moderate deformity has 15-20°IMA and severe deformity has more than 20°IMA [6]. Mathematical analysis revealed that distal metatarsal osteotomies (DMO) provide less corrective power than proximal metatarsal osteotomies (PMO).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A multitude of biomechanical studies have evaluated the initial stability of various metatarsal osteotomies, not only to determine which osteotomies permit early MTP joint exercises, but also to identify those which may allow early postoperative weight bearing [2,13,14,[18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%